A SIMPLE SCIENTIFIC FISH-LIVER OIL EXTRACTOR FOR PRODUCTION OF A-VITAMINISED OIL - Saha, K C (Indian Journal of Fisheries, 2015)
The need for large-scale production of vitaminised oil in India to meet the demand for cod-liver oil, now imported from foreign countries, cannot be over-emphasized. Recently, however, some of the State Governments have fostered the extraction of shark-liver oil as a substitute for imported codliver oil, more or less on cottage-industry scale: the credit for its extraction on a commercial basis, with the help of mechanised power plants, goes to the Department of Fisheries, Madras. Before the second world war, the market for shark-liver oil was very limited, although it was well known to be more potent with respect to its vitamin-A than cod-liver oil. But the interruption in the import of cod-liver oil on account of war forced the dealers and consumers to turn to the local substitute, so that during war time, a great pharmaceutical demand was created for shark-liver oil for making- vitamin-A concentrates, pharmaceutical emulsions, etc., in addition to its use as medicated oil as a source of vitamin-A in place of cod-liver oil.